Strategi Pemerintah Kota Surabaya Dalam Upaya Percepatan Penurunan Stunting - Viona Erlanda; Dida Rahmadanik (Aplikasi Administrasi: Media Analisa Masalah Administrasi, 2023)
Stunting is a failure of growth and development that disrupts the growth of toddlers due to continuous inadequate nutrition. Malnutrition during the growth period of children at an early age will hamper physical development, increase morbidity, and hinder children's mental development until death occurs. Whereas in toddlers it causes intellectual abilities and productivity to decrease. Currently, the stunting rate in Surabaya City is in the lowest position compared to other cities/districts throughout Indonesia. This study used a qualitative research method with a descriptive approach. This research focuses on knowing what strategies are used so that the success of the stunting reduction acceleration program in the Surabaya City Government occurs. Researchers conducted data analysis using the collaborative governance theory put forward by Ansell and Gash (2007) which focuses on collaborative processes. The data collection technique used secondary data obtained from news articles online and relevant journal articles. The data analysis technique involved data reduction, data presentation, and drawing conclusions. The results of the research show that the collaborative process in handling stunting is going quite well and effectively. This is proven by the decreasing in the number of stunting in the city of Surabaya, which decreases every year. Reducing stunting requires support from stakeholders, the organizations involved, and the people of Surabaya City. With this, it is hoped that the Surabaya City Government will be further motivated and continue to implement the program sustainably until there are no new cases of stunting.